Population Pharmacokinetics of Sotorasib in Healthy Subjects and Advanced Solid Tumor Patients Harboring a KRAS.sup.G12C Mutation from Phase 1 and Phase 2 Studies - Nagase, Mario; Houk, Brett; Vuu, Irene; Cardona, Panli; Dutta, Sandeep; Lin, Chih-Wei (The AAPS journal, 2025)
Sotorasib is a novel KRAS.sup.G12C inhibitor that has shown robust efficacy, safety, and tolerability in patients with KRAS.sup.G12C mutation. The objectives of the population pharmacokinetic (PK) analysis were to characterize sotorasib population PK in healthy subjects and patients with advanced solid tumors with KRAS.sup.G12C mutation from 6 clinical studies, evaluate the effects of intrinsic and extrinsic factors on PK parameters, and perform simulations to further assess the impact of identified covariates on sotorasib exposures. A two-compartment disposition model with three transit compartments for absorption and time-dependent clearance and bioavailability well described sotorasib PK. Sotorasib exposure increased in a less-than-dose proportional manner across the evaluated 180 mg to 960 mg dose range. Disease burden, measured by Eastern Cooperative Oncology Group (ECOG) score and baseline tumor size, were identified as significant covariates on clearance. Lower disease burden was associated with higher clearance (and thus lower sotorasib exposure). Low albumin was found to be associated with lower clearance of sotorasib. Use of PPIs was associated with reduced sotorasib exposures. Although sex, race, and high fat meal were significantly associated with PK parameters, their impact on exposures were not clinically relevant. Other evaluated covariates, including body weight, age, renal impairment (evaluated by chronic kidney disease stage score) and hepatic impairment (evaluated by NCI criteria) were not statistically significant. Greater baseline disease burden and low albumin were associated with lower sotorasib clearance; based on the established efficacy and safety profiles from clinical trials, the estimated magnitude of these effects does not warrant a dose adjustment. Graphical